Sur les fonctions arithmétiques - chami, abdessamed; Encadreur: Boudaoud, Abdelmadjid (UNIVERSITY of M'SILA, 2022)
This memoir consists of four chapters. The first one contains fundamental and necessary notions for those who want to start studying a number theory problem. Concepts related to arithmetic functions such as: Multiplicatively, additively, Dirichlet convolution product, Dirichlet inverses and the Moebius inversion formula, ... are the subject of the second chapter. The third chapter is devoted to summation methods, while the last chapter is devoted to the solution of some problems related to the subject and existing in the literature.
Keywords: Arithmetic functions, Euclidean Division, Prime number, Euclidean Algorithm, Integer parity, Dirichlet convolution product, Moebius inversion formula Summation.